The use of autonomy among physical education teachers in Finland and Kurdistan region of Iraq - Lagestad, Pål; Makrooni, Golaleh; Mohammed, Warhel Asim; Kalari, Joonas (Frontiers in Education, 2024)
IntroductionThe aim of the study was to examine fifth-grade physical education (PE) teachers’ reflections and perceptions about PE teaching in Finland and Kurdistan region of Iraq (KRI), using analyses of in-depth interviews with a phenomenological-hermeneutic approach.MethodsThis was accomplished by exploring eight Finnish and six KRI PE teachers’ opinions, attitudes, experiences, and reflections regarding their work as PE teachers, using semi-structured in-depth interviews about PE, as well as their reflections related to an indoor and an outdoor video from ordinary PE teaching in the other country. The initial analyses of the two groups of teachers using the qualitative analysis program NVivo revealed interesting findings related to student autonomy, and these differences were examined closely.ResultsWhile the analyses showed that all the Finnish PE teachers highlighted the importance of providing student autonomy within the open-ended questions related to PE, PE teachers in KRI seldom discussed autonomy during the open-ended questions. Instead, they seemed to organize their teaching in a way that decreased autonomy. The Finnish PE teachers indicated that the use of autonomy was central in the curriculum, and that they used autonomy to increase the students’ motivation and to make PE more meaningful for the students. With such a strategy, the use of autonomy would also activate and include more students, even if Finnish PE teachers reported certain challenges with students’ autonomy. The PE teachers from KRI, however, related PE to be mainly focused on performing sport activities and reflected a strategy of “just do as I do” - a strategy that created little room for autonomy, even if the findings pointed to some traces of autonomy among the PE teachers in KRI.DiscussionConsidering the findings and the theoretical concept of self-determination theory that highlight students’ autonomy as essential for students’ motivation, integration, wellness, and well-being in PE, our findings suggest that new perspectives and practices are needed among teachers in KRI to ensure autonomy in PE teaching. In this vein, increased exchange of experiences and collaboration between educators from Finland and KRI could be beneficial.